Efficacy of sacroiliac join infection with anesthetic and corticosteroid: a prospective observational study - Ab Aziz, Siti Nur Fudhlana; Zakaria@Mohamad, Zamzuri; Karupiah, Rajandra Kumar; Che Ahmad, Aminudin; Omar, Ahmad Sabri (2022)
Sacroiliac joint injection aims to provide pain relief, improve work status, and early return to work. We aimed to investigate the role of corticosteroid and anesthetic mixture to provide short- and long-term pain relief in patients with sacroiliac joint pain. This prospective observational study included 27 patients with sacroiliac joint dysfunction who received a combination of triamcinolone and ropivacaine for sacroiliac joint injection followed by three scheduled visits at four weeks, eight weeks, and six months. The pain was assessed using visual analogue scale (VAS), physician's assessment on the number of positive provocative tests, and patients' self-reported assessment to evaluate their functional outcome. At the four weeks and eight weeks follow up evaluations, the mean VAS reduced from 5.85 (±1.03) at baseline to 3.30 (±1.77) at four weeks, 3.30 (±1.86) at eight weeks, and 3.00 (±1.86) at six months. At each interval, improvement in terms of clinical assessment using a series of provocative tests was seen with a mean of 1.37 (±1.33), 1.63 (±1.31), and 1.48 (±1.05) at four weeks, eight weeks, and six months, respectively. For the functional effectiveness parameters (Roland-Morris questionnaires), the sacroiliac joint (SIJ) injected with these drugs combination showed a more significant improvement in symptoms and function, baseline (13.56±3.36), at four weeks (9.04±3.33), at eight weeks (9.07±4.13), and six months (8.26±4.92). Using the one-way repeated measures ANOVA, the SIJ pain, provocative test, and functional outcome significantly improved over time after injection with triamcinolone and ropivacaine (p<0.001). No complications of the administration of these medications were noted. Our finding support the intermediate-term (six months) effectiveness and safety of a combination of corticosteroid and anesthetic injection for patients with SIJ dysfunction who failed conservative treatment.